Prevalence of children born small for gestational age with short stature who qualify for growth hormone treatment - Gianluca Tamaro; Mariagrazia Pizzul; Giuliana Gaeta; Raffaella Servello; Marina Trevisan; Patricia Böhm; Paola Manera Ada Materassi; Anna Macaluso; Denis Valentini; Maria Chiara Pellegrin; Egidio Barbi; Gianluca Tornese (BMC, 2021)
Abstract Background Recombinant human growth hormone (rhGH) is approved in Europe as a treatment for short children born small for gestational age (SGA) since 2003. However, no study evaluated the prevalence of SGA children with short stature who qualify for rhGH in Europe so far. This study aimed to investigate in an Italian population the prevalence of children born SGA, of short stature in children born SGA, and of SGA children who qualify for rhGH treatment at 4 years of age. Methods We conducted a population-based study on primary care pediatricians' databases in Trieste, Italy. Data was collected on 3769 children born between 2004 and 2014. SGA was defined as birth weight and/or birth length ≤ − 2 SDS. Data on height and weight were registered at the closest well-being visit to 1, 2, 3, 4 years of age. Short stature was defined as height ≤ − 2 SDS. Short children born SGA who qualify for rhGH treatment were identified according to Note AIFA #39 criteria (age ≥ 4 years; height ≤ − 2.5 SDS; growth velocity < 50th percentile). Results Full data at birth were available for 3250 children. The SGA prevalence was 3.6% (0.8% SGA for weight, 2.2% SGA for length, 0.6% SGA for both weight and length). The prevalence of short stature among SGA children was 9% at 1 year of age, 6% at 2 years (significantly higher in preterm in the first 2 years), 4% at 3 years, 3% at 4 years (all born at term). At 4 years of age, median height SDS was − 0.52. One child born SGA was eligible for GH treatment (0.8% among SGA children). Conclusions The prevalence in a general pediatric population of children born SGA who qualify for GH treatment was 1:3250. Although the prevalence of SGA in our population was similar to previous studies, catch-up growth was recorded earlier in our sample compared to previous reports, and term babies had late catch-up. Height SDS of children born SGA at 4 years of age was lower than expected (− 0.52 SDS).